Concrete mathematics: A foundatioin for computer science - Graham, Ronald L.; Knuth, Donald E.; Patashnik, Oren (Boston Addison-wesley, 1994)
This book introduces the mathematics that supports advanced computer programming and the analysis of algorithms. The primary aim of its well-known authors is to provide a solid and relevant base of mathematical skills - the skills needed to solve complex problems, to evaluate horrendous sums, and to discover subtle patterns in data. It is an indispensable text and reference not only for computer scientists - the authors themselves rely heavily on it - but for serious users of mathematics in virtually every discipline.